Two-dimensional perovskite functionalized fiber-type heterostructured scintillators - Rogers, Edith; Birowosuto, Muhammad Danang; Maddalena, Francesco; Dujardin, Christophe; Pagano, Fiammetta; Kratochwil, Nicolaus; Auffray, Etiennette; Krause, Philip George; Bizarri, Gregory (American Institute of Physics (AIP), 2023)
A fiber-type heterostructured scintillator based on bismuth germanate (Bi4Ge3O12) functionalized with the 2D-perovskite butylammonium lead bromide ((BA)2PbBr4) has been fabricated, and its scintillation performance analyzed toward its use for fast timing applications such as time-of-flight Positron Emission Tomography. The pixel shows energy sharing between the matrix and filler component, confirming that the two components are in synergy.
Keywords: emission spectroscopy; heterostructures; radioluminescence; optical metrology; perovskites; scintillators; luminescence; metamaterials